2022
DOI: 10.1039/d2en00052k
|View full text |Cite
|
Sign up to set email alerts
|

Emerging investigator series: metal nanoparticles in freshwater: transformation, bioavailability and effects on invertebrates

Abstract: Increasing use of metal oxide-based nanoparticles (MNPs) and their release into the environment cast concerns about their environmental impacts. Massive efforts have focused on environmental behaviours and ecotoxicities to figure...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 249 publications
0
15
0
Order By: Relevance
“…Generally, NPs of smaller sizes displayed higher toxicity, thus the aggregates/agglomerates formed by the combination of AgNPs with NOM in surface water may play a key role in the toxicity difference (Hu et al, 2018). Additionally, our recent review also highlights the need for research on consideration of NPs toxicity with respect to natural water to better understand their bioavailability and biological effects (Wang and Liu, 2022). This is also the reason why Volvic® mineral water was used in the present study to simulate natural pond water (Auffan et al, 2018;Auffan et al, 2020).…”
Section: Introductionmentioning
confidence: 91%
See 3 more Smart Citations
“…Generally, NPs of smaller sizes displayed higher toxicity, thus the aggregates/agglomerates formed by the combination of AgNPs with NOM in surface water may play a key role in the toxicity difference (Hu et al, 2018). Additionally, our recent review also highlights the need for research on consideration of NPs toxicity with respect to natural water to better understand their bioavailability and biological effects (Wang and Liu, 2022). This is also the reason why Volvic® mineral water was used in the present study to simulate natural pond water (Auffan et al, 2018;Auffan et al, 2020).…”
Section: Introductionmentioning
confidence: 91%
“…The measured environmental concentration of AgNPs range from 0.3 to 3200 ng/L in surface waters (Zhao et al, 2021). To date, numerous studies reported the effects of NPs on freshwater gastropods (Caixeta et al, 2020;Wang and Liu, 2022). However, only few studies investigated the AgNP effects on L. stagnalis, focusing solely on bioaccumulation and memory formation (Wang and Liu, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nanomaterials possess unique physicochemical properties that distinguish them from bulk materials and ions, owing to their small size and large surface area. It remains an open question about whether the effects of nanomaterials on living organisms and human health are unique or like either their bulk materials or ions. Addressing this crucial question effectively would enable rational design of regulatory guidelines of nanomaterials for safe handling and manufacturing of nanomaterials and accelerating safe applications of nanomaterials and nanotechnology. Notably, toxic effects of heavy metals and their ions have been widely studied over decades.…”
Section: Introductionmentioning
confidence: 99%